Implementation of Structure Simplification Policy At Syarif Hidayatullah State Islamic University Jakarta - Farida Hidayati; Ambar Setyaningsih; Ashep Ramdhan Noermansyah; Maya Puspita Dewi; Taufiqurokhman Taufiqurokhman (Jurnal Indonesia Sosial Teknologi, 2024)
UIN Syarif Hidayatullah Jakarta has implemented policies related to simplifying organizational structures by Regulation Manteri Utilization State Apparatus and Bureaucratic Reform number 25 of 2021 concerning Simplification of Organizational Structures in Institutions. According to Charles O Jones, the success of policy implementation can be seen from 3 things, namely: (1) Organization, (2) Interpretation, and (3) Application. From the results of existing secondary data analysis, the implementation of policies related to simplifying the organizational structure has been carried out well where, in terms of organization, UIN Syarif Hidayatullah has made structural adjustments by eliminating echelon III and IV administrative positions, transferring them to functional positions. Apart from that, UIN Syarif Hidayatullah Jakarta has also implemented a working team as a result of the simplification of the structure, where the working team was formed to achieve certain activity targets. In terms of interpretation, UIN Syarif Hidayatullah Jakarta has also implemented strategic steps in implementing the structure simplification policy, namely: (1) mapping of organizational units, (2) submitting mapping results to leadership and (3) verification and validation of mapping. If the implementation of the structure simplification policy was carried out after the Regulation of the Minister of Religion was issued, there was a change in the organizational structure which was followed by the elimination of echelon III and IV administrative officials into functional positions and the formation of work teams to support the achievement of organizational performance. In its implementation, there are still obstacles where the functional position groups resulting from the equalization have not been able to carry out their functions optimally because they require time to adjust to the duties and functions of their new positions and the competency standards that should be possessed by functional officials have not been met. Increasing competency for functional officials as a result of equalization should be a common concern to improve organizational performance.